Diet related disorders obesity, type 2 diabetes and coeliac disease - Verso, Nicholas; Rutigliano, Katrina; Video Education Australasia (Australia : VEA, 2010)
Knowledge of nutrition is integral to making healthy food choices. This program examines three diet-related disorders, looking in detail at the characteristics, causes, treatment and strategies for prevention. It explores recent developments in food aimed at enhancing health, the impact of food consumption on nutrition, and ways of meeting food requirements to maintain optimum health and wellbeing.
Director of phothography, Charlie Sarroff; Ben Milward-Bason.
Presenter: Chantal Bui Viet.
Keywords: Nutrition Therapy; Obesity; Diabetes Mellitus, Type 2.; Celiac disease